ARCHAEOLOGICAL, ARCHITECTURAL AND VEGETAL METAPHORS OF POSTCOLONIAL BRITISH IDENTITY IN V. S. NAIPAUL’S THE ENIGMA OF ARRIVAL - Dr. Angela STĂNESCU (Diversitate si Identitate Culturala in Europa, 2012)
V. S. Naipaul’s The Enigma of Arrival is a classic postcolonial autobiography, mapping out the geographical and cultural journey of the postcolonial migrant towards the mythologized centre of civilization, the imperial metropolis. In his Wordsworthian contemplation of rural England as a utopian site of natural, historical and cultural ‘piety’, Naipaul retraces the inscriptions of a teleological myth of Englishness underlying the grand historical narrative of the Empire and the utopian imagination of the colonial subject’s mindscape. The present paper examines Naipaul’s deployment of the symbolical valences of English archaeological sites, of architectural and garden landscapes in rewriting his own, as well as Britain’s, postcolonial identity. The analysis highlights the historical and ideological significations of the consistent architectural and vegetal conceits of imperial glory and decay, informing this highly poeticised enactment of the colonial migrant’s repositioning in the changing cultural landscape of post-imperial Britain.